2017
DOI: 10.1186/s12885-017-3362-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding why cancer patients accept or turn down psycho-oncological support: a prospective observational study including patients’ and clinicians’ perspectives on communication about distress

Abstract: BackgroundInternational standards prioritize introducing routine emotional distress screening in cancer care to accurately identify patients who most need psycho-oncological treatment, and ensure that patients can access appropriate supportive care. However, only a moderate proportion of distressed patients accepts referrals to or uses psycho-oncological support services. Predictors and barriers to psycho-oncological support service utilization are under-studied. We know little about how patients and oncologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…We report findings from a prospective, observational study in the Oncology Outpatient Clinic of the University Hospital Basel (Switzerland). Our methods are briefly outlined below; we have described them in more detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…We report findings from a prospective, observational study in the Oncology Outpatient Clinic of the University Hospital Basel (Switzerland). Our methods are briefly outlined below; we have described them in more detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…In Switzerland, a study investigating the barriers and predictors of patients accepting or declining psycho-oncological support has recently opened. The results of this trial should increase the insight into why not all patients with PD want to be referred for an intervention [38].…”
Section: Discussionmentioning
confidence: 99%
“…The Akizuki study outlined above was followed up by a screening trial, in which of the 37% of patients identified as being distressed, 93% received a recommendation from their attending physician for a psycho‐oncology service consultation, but only 25% accepted the referral . As such, there is a need to understand oncology patient preferences for being offered, and barriers to accepting, referrals to psychosocial services . This study describes among oncology patients undergoing radiotherapy (RT): the proportion who are likely to be experiencing symptoms of depression or anxiety, as identified by 3 brief measures (a standardised brief assessment tool [HADS]; single items assessing patients' perceptions [ultrashort tool]; and single items assessing judgements of the patient's radiation oncologist); the proportion of patients who would like to be offered professional support for their current levels of depression and anxiety (and reasons for not wanting this); and agreement between the HADS and ( a ) single‐item patient‐reported assessments of their depression and anxiety and ( b ) clinician judgements of anxiety and depression. …”
Section: Introductionmentioning
confidence: 99%